Analisis Dampak Penebangan Hutan Adat Kemenyan di Pandumaan, Humbang Hasundutan: Sebuah Pendekatan Restorasi Ekologi - Aldo Maruli Tua Sianturi; Bestian Simangunsong; Tiffany Tamba; Bernhardt Siburian; Nurelni Limbong (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
The destruction of the incesce customary forest in Pandumaan village and the conflict over customary land with PT Toba Pulp Lestari (TPL) have damaged the preservation of the incesce customary forest. This condition really needs attention and restoration. Frankincense trees are continuously cut down by the company. Frankincense trees and other natural wood in the forest are cleared using a clear-cutting system and the logging areas are immediately planted by PT.TPL. The research method in this study uses qualitative descriptive analysis research methods. The author will conduct a special investigation regarding ecological restoration proposed by Van Wearen. Qualitative research in data collection is carried out using primary data sources, and data collection techniques will look for literature reviews, books, news and journals by collecting data from various literature. Restoring customary forests is also healing God's creation which has been damaged by humans. Understanding of ecological restoration as a basis for restoring the traditional incesce forest in Pandumaan village. The traditional forest of Pandumaan Village is a beautiful creation of God that should be protected and preserved.